Research and development investment and operational performance of listed small and medium-sized enterprises in China. Issue 54 (19th November 2020) - Su, Wunhong; Song, Xiaobao; Guo, Chun
ABSTRACT: This study aims to investigate the impact of research and development (R&D) investment on the operational performance of small and medium-sized enterprises (SMEs) from 2013 to 2017. The findings show that there is a significant negative relation between R&D investment and the operational performance of SMEs in China. This negative effect lasts for three years subsequent to R&D investment. In addition, there is no positive relation between R&D investment and the operational performance of SMEs. The relation between R&D investment and operational performance appears significantly negative for non-state-owned enterprises (non-SOEs) and SMEs with an R&D investment intensity of more than 5%. However, it is non-significant for state-owned SMEs (SOEs) and SMEs with an R&D investment intensity of less than 5%. The two-stage method of the Heckman test and propensity score matching (PSM) are employed in this study to exclude problems of endogeneity, and the results remain robust.